2021
DOI: 10.1002/ajmg.a.62122
|View full text |Cite
|
Sign up to set email alerts
|

Maternal health and pregnancy outcome in diagnosed and undiagnosed Marfan syndrome: A registry‐based study

Abstract: In Marfan syndrome (MFS), pregnancy is considered as high risk due to the deficiency of fibrillin in the connective tissue and increased risk of aortic dissection. The objective was to demonstrate the consequences on maternal health, in women with diagnosed and undiagnosed MFS at the time of pregnancy and childbirth. By using national health care registries, we identified all pregnancy related outcomes, from women with MFS (n = 183) and an age‐matched background population (n = 18,300). We found 91 pregnancies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In 113 of these reports, the prognostic significance of the time of diagnosis was emphasized, however without direct evidence. Only 6 studies measured the time of diagnosis 6, 11, 16–19 : One study used questionnaires to examine the time between the first symptoms and the final diagnosis in 430 patients 16 . Another retrospective study of 66 adults with MFS compared outcomes of 27 patients with a diagnosis before and 39 with a diagnosis after the onset of adulthood 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 113 of these reports, the prognostic significance of the time of diagnosis was emphasized, however without direct evidence. Only 6 studies measured the time of diagnosis 6, 11, 16–19 : One study used questionnaires to examine the time between the first symptoms and the final diagnosis in 430 patients 16 . Another retrospective study of 66 adults with MFS compared outcomes of 27 patients with a diagnosis before and 39 with a diagnosis after the onset of adulthood 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of administrative data from 389 patients with MFS, the delay in diagnosis was measured in days from the first symptoms to the final diagnosis 18 . Finally, three Danish studies with administrative data reported age at initial diagnosis 11 , time of diagnosis in relation to aortic events 6 , and pregnancy (Table S6) 19 . EURORDIS, not listed in Medline, measured diagnostic delays using questionnaire responses of 682 families with MFS 20 .…”
Section: Discussionmentioning
confidence: 99%